Design and Development of Simple and Low-cost Light Source for Laparoscopic Surgery - Chhetri, Dikshya; Bhandari, Shruti; Shahi Thakuri, Aishwarya; Pokharel, Aayushma; Poudel, Paras (Journal of Nepal Health Research Council, 2022)
Background: The existing medical light source device used in laparoscopy surgery is very costly and is not yet developed in Nepal. This study aimed to build a light source device that is cost-effective and passes all the testing parameters like Light Emitting Diode illumination, color, and heat. Methods: A method of constructing a light source comprises the steps of designing, assembling the system, and undergoing device testing. The design of the device was done through Sketchup software. The dual switched-mode power supply of 3-4 Voltage to the Light Emitting Diode and 12 Voltage to the rest of the system with cooling technology were used. Results: The Light emitted from the Light Emitting Diode focuses the light directly at the fiber optic cable through the coupler. Moreover, the testing of the device concludes that the increment temperature of the device for 1 hour is 1 degree Celsius whereas the maximum increment temperature was found to be 3 degrees. Additionally, the fiber optic illumination at the port is found to be >50000. Also, the color of the Light Emitting Diode is cool white light having a color temperature of 5700 Kelvin and a color rending index of 92. Conclusions: The developed device is four times cheaper than a similar device available in the Nepalese market. Also, this device has been developed first of its kind in Nepal. Keywords: Light emitting diode; light source; low-cost